The third book of general ignorance - Lloyd, John, 1951-; Mitchinson, John, 1963-; Harkin, James (Television researcher); Murray, Andy (Andrew Hunter) (Faber & Faber, 2015)
The Third Book of General Ignorance gathers together 180 questions, both new and previously featured on the BBC TV "QI" programme's popular 'General Ignorance' round, and show why, when it comes to general knowledge, none of us knows anything at all. Who invented the sandwich? What was the best thing before sliced bread? Who first ate frogs' legs? Which cat never changes its spots? What did Lady Godiva do? What can you legally do if you come across a Welshman in Chester after sunset?